2020
DOI: 10.4236/ojped.2020.102025
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Dysplasia of the Hip: Management of Graf IIa Dysplastic Hip

Abstract: Developmental Dysplasia of the Hip (DDH) describes a wide range of anatomic abnormalities of the growing hips which might result in permanent abnormal gait. Therefore, early detection and management is crucial to improve the outcome and minimise the risk of osteoarthritis in later life. Hip ultrasound is used to evaluate DDH based on Graf classification. Graf score is a widely used ultrasound grading score to evaluate DDH in infants. There is conflicting evidence regarding the management of the developmentally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Developmental dysplasia of the hip (DDH) encompasses a wide spectrum of pathology, ranging from complete fixed dislocation at birth to asymptomatic acetabular dysplasia in adulthood [ 1 ], which can negatively affect hip development and can lead to isolated acetabular dysplasia, subluxation, complete dislocation of the hip joint, or permanent abnormal gait [ 2 , 3 ]. The children with untreated persistent DDH may suffer from pain due to a series of anatomical changes such as increased abnormal articular pressure or increased tension on a smaller contact area during the process of growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Developmental dysplasia of the hip (DDH) encompasses a wide spectrum of pathology, ranging from complete fixed dislocation at birth to asymptomatic acetabular dysplasia in adulthood [ 1 ], which can negatively affect hip development and can lead to isolated acetabular dysplasia, subluxation, complete dislocation of the hip joint, or permanent abnormal gait [ 2 , 3 ]. The children with untreated persistent DDH may suffer from pain due to a series of anatomical changes such as increased abnormal articular pressure or increased tension on a smaller contact area during the process of growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…[10] However, another study reported a prevalence ranging from 5% to 12%, which is in line with our findings. [11] This suggests that the inconsistency in ranges might be attributed to the different timing of US examination. The results of the current study revealed that 45% of infants with DDH exhibited bilateral involvement.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 8 ] The screening of infants suspected of having DDH lacks consensus and comprehensive studies. [ 9 11 ] In Saudi Arabia, the practice of screening newborns with US is not yet commonplace. Therefore, this study investigated the incidence of DDH among infants at King Abdul-Aziz University in Jeddah to better understand the DDH incidence rate and emphasize the importance of screening newborns using US.…”
Section: Discussionmentioning
confidence: 99%
“…The alpha angle consists in the bony roof angle, and the beta angle consists in the cartilage roof angle. According to this method, type I hips are considered mature, whereas type III hips are considered immature [ 6 ]. To treat DDH, experts recommend a noninvasive approach that focuses on timely interventions such as splints, braces, and harnesses that are tailored to the age and severity of the condition [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%